2007
DOI: 10.1111/j.1365-2648.2007.04279.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of informed consent: a pilot study

Abstract: This study strengthened the perception that more extensive research about research participants is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…First, among respondents, our finding that a personal connection to breast cancer served as a principal driver to decision-making to enroll in the MMHS corresponds well with the literature showing that family cancer history (22) and illness of a friend or relative (23) can serve as motivation for participation in medical research. In the epidemiology literature, a personal connection to breast cancer is reported as a strong motivator for participation in research, as women who participated in a breast cancer prevention trial were observed to be “keenly aware of their responsibility to others” and stated that they took part in hopes of preventing breast cancer in future generations (24).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…First, among respondents, our finding that a personal connection to breast cancer served as a principal driver to decision-making to enroll in the MMHS corresponds well with the literature showing that family cancer history (22) and illness of a friend or relative (23) can serve as motivation for participation in medical research. In the epidemiology literature, a personal connection to breast cancer is reported as a strong motivator for participation in research, as women who participated in a breast cancer prevention trial were observed to be “keenly aware of their responsibility to others” and stated that they took part in hopes of preventing breast cancer in future generations (24).…”
Section: Discussionsupporting
confidence: 80%
“…Investigators are now challenged to comply with the HIPAA regulations and wording and balance those requirements with the need to relay the study purpose in a way that a layperson can truly understand. As with other studies (23), focus group participants reported confusion after reading the consent form and this did serve as a barrier to participation or at least gave cause for concern. Some focus groups participants asked that a paragraph explaining the study purpose and the basic concepts presented in the consent form be summarized on the front of the consent in layman's terms, which was provided by the study investigators (see materials).…”
Section: Discussionsupporting
confidence: 51%
“…The questionnaire was self-administered and tested in a pilot study [9]. The key elements of informed consent were defined as follows: information, understanding, competence, voluntariness, and decision-making.…”
Section: Methodsmentioning
confidence: 99%
“…The main function of RECs in the UK is to ensure that safeguards are in place to protect research participants from harm (Schüklenk 2000, WMA 2000, DoH 2005, SEHD 2006), a function which is based primarily on the principle of non‐maleficence. Informed consent by research participants is the pre‐condition incorporated in a range of international guidelines for any ethical research which exists to protect them from harm whilst respecting their autonomy (Doyal 1997, Schüklenk 2000, WMA 2000, Länsimies‐Antikainen et al. 2007).…”
Section: Ethical Tensionsmentioning
confidence: 99%